CONTENT OF A SPECIAL COURSE ON HIGH PERFORMANCE COMPUTING - Serik М.; Yerlanova Г.Ж (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
At present, along with the dynamic development of computer technology in the world, the most effective ways of solving problems of practical importance are being considered. High performance computing takes the lead in this. Therefore, the development of modern society is closely related to the training of experienced, modern specialists in the field of information technology. This, in turn, depends on the inclusion of new courses in the curriculum and full coverage of these issues in the content of the taught courses. This article analyzes the courses on high performance computing, taught at experimental bases and abroad, on the basis of this, the topics of the special course and the content recommended for implementation in the educational process are determined. During the training, the competencies of students in high performance computing were identified.